2009
DOI: 10.1111/j.1365-2672.2009.04638.x
|View full text |Cite
|
Sign up to set email alerts
|

The feasibility of developing a risk assessment for the impact of climate change on the emergence of Crimean-Congo haemorrhagic fever in livestock in Europe: a Review

Abstract: Summary Crimean‐Congo haemorrhagic fever virus (CCHFV) is one of the most widespread of all medically important arboviruses with ticks of the Hyalomma spp. serving as the main vectors. Infection of livestock by CCHFV serves as a route of exposure to humans, as a reservoir of disease and as a route of importation. This study discusses the pathways and data requirements for a qualitative risk assessment for the emergence of CCHFV in livestock in Europe. A risk map approach is proposed based on layers that includ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
53
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 33 publications
(53 citation statements)
references
References 45 publications
0
53
0
Order By: Relevance
“…In this respect, the predictions from the current model may be too high because no allowance is made for failure of some of those larvae to survive and moult. Second, layers on the habitat suitability for H. marginatum (layer 3 in Gale et al 2010) and on the density of small mammal hosts, for example, hares, (layer 4 in Gale et al 2010) are not required for this incursion model. The value of p find will vary depending on the terrain and will also be affected by the species of birds which introduced that tick and in particular its favoured habitat and hence proximity to livestock.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…In this respect, the predictions from the current model may be too high because no allowance is made for failure of some of those larvae to survive and moult. Second, layers on the habitat suitability for H. marginatum (layer 3 in Gale et al 2010) and on the density of small mammal hosts, for example, hares, (layer 4 in Gale et al 2010) are not required for this incursion model. The value of p find will vary depending on the terrain and will also be affected by the species of birds which introduced that tick and in particular its favoured habitat and hence proximity to livestock.…”
Section: Discussionmentioning
confidence: 99%
“…The risk pathway is taken from Gale et al (2010) and involves three layers: l Layer 1 -abundance of migratory birds to predict the release of CCHFV through infected Hyalomma nymphs carried on migratory birds; l Layer 2 -temperature to predict the moult of nymphs to adult ticks; and l Layer 3 -Livestock density to estimate the probability of an adult tick finding a livestock host to feed upon.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Infestation of the immature stages of the ticks by small animals such as rabbits, hares, hedgehogs and rodents assist the maintenance of the virus in the lifecycle of the ticks (Gonzalez et al, 1992;Gargili et al, 2013). Feeding on the ground-dwelling birds, hares and hedgehogs drives larval and nymphal ticks to become infected with CCHFV, (Gale et al, 2010), while the adult ticks become infected while feeding on infected sheep, goats, cattle and pigs (Gale et al, 2010). Most species of birds play role as mechanical vectors in transportation of infected ticks, and appear to be refractory to CCHFV infection; but experimental studies in Ostriches have revealed the presence of the virus in for up to 1 to 4 days in blood and 5 days in visceral organs (Center for Food Security and Public Health (CFSPH), 2007).…”
Section: Host Range and Vector Involvedmentioning
confidence: 99%